Utilizing Geographic Information Systems to Estimate Biomass and Carbon Based on Slope in Secondary Dryland Forests in the Forest Area of Mulawarman University - Adelia Juli Kardika; Julian Istanto; Khilma Sufiana; Agustina Murniyati; Kiamah Fathirizki Agsa Kamarati; Rudito (Politeknik Pertanian Negeri Samarinda, 2023)
Calculation of standing biomass is usually carried out using linear and non-linear regression equation models based on the type of plant or tree resulting from field measurements. The aim of this study was to estimate the estimation of biomass and carbon based on the slope of the secondary forest in the KHDTK educational forest of Mulawarman University. Mulawarman University Educational Forest. Data collection to calculate biomass and carbon stocks obtained by direct measurements in the field and utilizing the Geographic Information System. The results of the highest biomass estimation at the sapling level are on a slope of 25-45% with an average value of 12.599 tons/ha; at the pile level with a slope of 25-45% the average value is 28.412 tons/ha; at the tree level with a slope of 8-15% the average value is 155.024 tons/ha; and in a litter with a slope of 25-45% the average value is 38.12 tons/ha. The greatest potential carbon yield is at the sapling level with a slope of 25-45% with an average value of 6.300 tons/ha; at the pile level with a slope of 25-45% the average value is 14.206 tons/ha; at the tree level with a slope of 8-15% the average value is 77.512 tons/ha; and in litter with a slope of 25-45% the average value is 17.86 tons/ha.